2021
DOI: 10.1177/14733250211051410
|View full text |Cite
|
Sign up to set email alerts
|

Managing role expectations and emotions in encounters with extremism: Norwegian social workers’ experiences

Abstract: To prevent radicalisation and violent extremism, many European countries have adopted a multiagency approach, consisting of both police, teachers and social workers. Such strategies have caused concern for a securitization of social policy and stigmatization of vulnerable groups. This study aims at gaining insight into how Norwegian social workers involved in prevention work against violent extremism experience and manage role conflicts and emotions during interaction with their clients. This article presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Thirteen studies presented data that illustrated how effective supervision, oversight and quality assurance facilitated implementation (Spalek et al, 2010; Becker et al, 2014; Christensen, 2015; Schuurman & Bakker, 2016; Hofinger & Schmidinger, 2017; van der Heide & Schuurman, 2018; Schuhmacher, 2018; AEF, 2018; Orban, 2019; Haugstvedt, 2022; Pettinger, 2020a; Haugstvedt & Gunnarsdottir, 2023; Cherney et al, 2022; Sizoo et al, 2022). This finding was most clearly emphasised by Haugstvedt (2022), who reported that social workers had an ‘outspoken need for supervision and professional guidance’ (p. 172).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies presented data that illustrated how effective supervision, oversight and quality assurance facilitated implementation (Spalek et al, 2010; Becker et al, 2014; Christensen, 2015; Schuurman & Bakker, 2016; Hofinger & Schmidinger, 2017; van der Heide & Schuurman, 2018; Schuhmacher, 2018; AEF, 2018; Orban, 2019; Haugstvedt, 2022; Pettinger, 2020a; Haugstvedt & Gunnarsdottir, 2023; Cherney et al, 2022; Sizoo et al, 2022). This finding was most clearly emphasised by Haugstvedt (2022), who reported that social workers had an ‘outspoken need for supervision and professional guidance’ (p. 172).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies identified potential conflicts that can emerge when different partners are rooted in differing organisational contexts and cultures and/or lack an understanding of partners' organisational culture(s) (Weggemans & de Graaf, 2017; Hellevik et al, 2022; Raets, 2022; Haugstvedt & Gunnarsdottir, 2023; Sizoo et al, 2022; Kotzur et al, 2022; Stern et al, 2023). A common issue was the discomfort that practitioners working in non‐security sectors might experience when engaging with security actors, which may require them to share information about individuals to whom they have a duty of care (Haugstvedt & Gunnarsdottir, 2023; Raets, 2022). This issue was discussed in the context of mental healthcare, with practitioners from other sectors noting how engaging with mental health practitioners can be challenging due to a lack of training, or willingness to work with violent extremists (Hellevik et al, 2022; Sizoo et al, 2022; Stern et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The examples of crisis interactions analysed in this article have shown how the security context in which the pedagogues act can influence the work of project employees and create situations in which excessive demands are placed on them unwillingly through diffuse feelings of being threatened and latent fears, especially when security questions and dangers are taboo or it remains unclear whether a client is in fact prone to violence or is merely labelled as 'radical'. This reveals the fact that their work includes 'emotional labour' (Hochschild, 1983, p. 7), excluding negative feelings or emotional dissonance, suppressing feelings or -in other situations -using them in a targeted way (Haugstvedt and Gunnarsdottir, 2021;Herland, 2021;Moesby-Jensen and Nielsen, 2015). The basis for this could be a conscious and targeted engagement with one's own emotions, as well as the emotional dynamics within the relationship to and communication with the clients.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…The international publications explicitly investigating the point of view of professionals in the field have mainly addressed sectors other than the penal circuit, mainly in the area of educational and social intervention (Haugstvedt and Gunnarsdottir 2023;Mattsson 2018;Vallinkoski and Benjamin 2023;Van de Weert and Eijkman 2019, 2020a, 2020b, or schools (Holmberg 2021;Sjøen and Mattsson 2020), in several, mainly northern European countries (Norway, Sweden, Holland, and Finland). These studies analysed the ways in which professionals perceive the phenomenon of violent radicalism and how it affects their everyday work.…”
Section: For a Situated Approach To The Study Of Violent Radicalisationmentioning
confidence: 99%
“…An interesting point that emerges from these articles concerns the conflict, experienced by the operators, between the securitarian attitudes disseminated through public and institutional discourses and, consequently, in the formal directives and guidelines to which they are also called upon to respond, on the one hand, and the educational mandate and deontological indications that characterise the daily work of professionals, on the other. This conflict may reach the point at which professionals experience considerable emotional strain (Haugstvedt and Gunnarsdottir 2023). Moreover, it is precisely the adoption of a securitarian register and the segregationist dynamics associated with it that are described as a possible, albeit indirect, cause of the radicalisation process (Mattsson 2018).…”
Section: For a Situated Approach To The Study Of Violent Radicalisationmentioning
confidence: 99%